The Dissonant Duet: An Autoethnography of a Teacher-Student Relationship - Gouzouasis, Peter; Ihnatovych, Diana (Journal of the Canadian Association for Curriculum Studies, 2016)
In reading the research available on the topic of teacher-student relationships in learning, it is evident that over the past four centuries very little has changed in traditional, individual music lessons. Through an exploration of the research literature, we came to realize that it is difficult to describe the socioemotional aspects of learning using traditional research methods, and there are many aspects of learning that are beyond explanation in quantitative, realist-styled studies of the efficacy of learning techniques, learning outcomes, evaluation, motivation, literacy, and technical competency. While we began with our inquiry with an interest in studying traditional piano pedagogy, a complex journey led us to using autoethnography as a way to share and demystify a taboo story from the piano studio that extends beyond music learning. Ours is a sensitive story to tell, and the risks involved in discussing this topic in pedagogical contexts have kept many learners silenced for decades. Through this process, we have learned that when autoethnography is considered as a form of pedagogy, it is an evocative way to reveal and describe subjective, yet crucial, aspects of learning.